Two-state teleportation - Henderson, L; Hardy, L; Vedral, V (American Inst of Physics, 2000)
Lower bounds for two-state teleportation fidelity were computed using a nonmaximally entangled pure state as a channel, and the exact result for the two-state fidelity with no entanglement. Only pure entangled states were considered as channels for teleportation. The results provide additional information on the respective roles of classical information and quantum entanglement in the new field of quantum information processing.